Biology laboratory completeness analysis in high school - Nurul Aulia; Luthfiana Nurtamara; Laila Munada; Muhammad Rifani Arsyad; Ni Komang Ayu Purwanti; Rumaisha Zahra Hanifa Rokhima (Practice of The Science of Teaching Journal: Jurnal Praktisi Pendidikan, 2025)
Practical activities are an inseparable part of biology learning, because through practical work, students will prove concepts or theories that have been obtained through a series of experimental processes so that they can support students in understanding learning materials. The existence of a biology laboratory that supports the success of the biology teaching and learning process must of course meet the minimum requirements for the establishment of a laboratory related to the completeness of tools and facilities in accordance with the standards of educational facilities and infrastructure. The purpose of this study was to analyze the completeness of the chemistry laboratory at SMA Negeri 1 Alalak. Laboratory analysis based on standard facilities and Permendiknas RI No. 24 of 2007. The method used in this research is the descriptive method with a quantitative approach. The school subjects used in this study were SMA Negeri 1 Alalak. The results of the analysis of the completeness of the chemical laboratory at SMA Negeri 1 Alalak showed that 85.8% of the furniture used for practicum was available in the laboratory, while the suitability of the equipment used was 78.2%. For consumables stored in the laboratory as a whole by existing standards (100%), and as much as 100% of other available equipment, so the analysis results show that the chemical laboratory equipment owned by SMA Negeri 1 Alalak is by the standard of facilities. and laboratory infrastructure in this case Permendiknas RI No. 24 of 2007. Abstrak. Kegiatan praktikum merupakan bagian yang tak terpisahkan dalam pembelajaran biologi, karena melalui praktikum peserta didik akan membuktikan konsep atau teori yang sudah didapat melalui serangkaian proses percobaan sehingga dapat menunjang peserta didik untuk memahami materi pembelajaran. Keberadaan laboratorium biologi yang mendukung keberhasilan proses belajar mengajar biologi tentu harus memenuhi syarat minimal berdirinya laboratorium terkait kelengkapan alat dan sarana sesuai dengan standar sarana dan prasarana pendidikan. Tujuan penelitian ini adalah menganalisis kelengkapan laboratorium Biologi di SMA Negeri 1 Alalak. Analisis laboratorium berdasarkan standar sarana dan prasarana dan Permendiknas RI No. 24 Tahun 2007. Metode yang digunakan dalam penelitian ini adalah metode deskriptif dengan pendekatan kuantitatif. Subjek sekolah yang digunakan dalam penelitian ini adalah SMA Negeri 1 Alalak. Hasil analisis kelengkapan laboratorium biologi di SMA Negeri 1 Alalak menunjukkan bahwa perabot yang digunakan untuk praktikum tersedia di laboratorium sebesar 85,8%, sedangkan kesesuaian peralatan yang digunakan sebesar 78,2%. Untuk bahan habis pakai yang tersimpan di laboratorium secara keseluruhan sesuai dengan standar yang ada yaitu 100%, dan sebanyak 100% dari peralatan lain yang tersedia, maka hasil analisis menunjukkan bahwa peralatan laboratorium biologi yang dimiliki SMA Negeri 1 Alalak sudah sesuai dengan standar sarana dan prasarana laboratorium dalam hal ini Permendiknas RI No. 24 Tahun 2007.